2015
DOI: 10.1111/jphp.12423
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in oral bioavailability and dissolution of tanshinone IIA by preparation of solid dispersions with porous silica

Abstract: SDs with porous silica as carrier could achieve superior oral bioavailability by improving drug dissolution, whereas drug stability could be maintained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…37 Sylysia 350, a common type of PSi, with pore size at 21.0 nm and pore volume at 1.6 mL g À1 , has many silanol groups on its surface and can be applied as a pharmaceutical excipient for oral administration because of its good biocompatibility, stability, and nontoxicity. 7,53 In addition, it has an excellent capacity to improve the powder properties and the dissolution of drugs. Therefore, PSi is widely used as a carrier to enhance various properties of drugs in pharmaceutical eld.…”
Section: Porous Silica (Psi)mentioning
confidence: 99%
See 4 more Smart Citations
“…37 Sylysia 350, a common type of PSi, with pore size at 21.0 nm and pore volume at 1.6 mL g À1 , has many silanol groups on its surface and can be applied as a pharmaceutical excipient for oral administration because of its good biocompatibility, stability, and nontoxicity. 7,53 In addition, it has an excellent capacity to improve the powder properties and the dissolution of drugs. Therefore, PSi is widely used as a carrier to enhance various properties of drugs in pharmaceutical eld.…”
Section: Porous Silica (Psi)mentioning
confidence: 99%
“…Recently, there are many literatures reported that PSi combined with the SD technology (PSi-SD) achieved preferable solubilization of drugs. 7,[53][54][55] For example, Yan et al 7 reported that tanshinone IIA (tanIIA) in PSi-SD with different ratios (1 : 2 to 1 : 8) showed signicantly improved dissolution rates ($4-fold at maximum) compared to pure tanIIA and corresponding physical mixtures. Besides, the AUC 0-24 h of tanIIA from PSi-SD increased by 1.97 times compared with pure tanIIA, demonstrating that its oral bioavailability was improved by SD with PSi.…”
Section: Porous Silica (Psi)mentioning
confidence: 99%
See 3 more Smart Citations